THE IMPACT OF HELICOPTER PARENTING ON PSYCHOLOGICAL DEPENDENCY - Gulomjonovich Tolibov, Elchin (GOLDEN BRAIN, 2024)
This article aims to examine the impact of helicopter parenting on psychological dependency. Helicopter parenting is characterized by parents’ excessive interference in their children’s lives and the restriction of their independence. This parenting style can lead to psychological dependency, loss of self-confidence, and other developmental issues. The study discusses the negative effects of helicopter parenting on children’s independence and its role in the development of psychological dependency in adulthood. The findings suggest that helicopter parenting may contribute to the development of psychological dependency.